Drug Delivery Using Stimuli-Responsive Polymer Gel Spheres - Ninawe, Pravin R; Parulekar, Satish J (Industrial & engineering chemistry research, 2012)
Polymeric gels that undergo deformation upon appropriate changes in pH or temperature have considerable promise as drug delivery vehicles. Uptake of drug macromolecules into swelling and nonswelling gel spheres and release of drug macromolecules from deswelling and nondeforming gel spheres into a target fluid are investigated here. A mathematical model for gel–solution composite, a composite of a distributed parameter system (gel spheres) and a lumped parameter system (surrounding solution), is developed. The polymer network displacement in swelling/deswelling gels is described by a stress diffusion coupling model. The analytical solution for network displacement is used to predict solvent intake by swelling gels, solvent efflux from deswelling gels, and changes in pressure, porosity, and effective drug diffusivity resulting from network displacement. These in turn influence drug uptake during and after gel swelling and drug release from gel during and after gel deswelling. Numerical results illustrate benefits of gel swelling for drug loading and merits of different modes of drug release. Comparisons are made, as concerns drug uptake and drug release, with gels not subject to deformation.